PHARMACEUTICAL EQUIVALENCE AND COMPARATIVE BIOAVAILABILITY OF MULTISOURCED ARTESUNATE AND AMODIAQUINE TABLETS IN SOUTH WESTERN NIGERIA (2011)
Malaria is one of the most devastating parasitic diseases in the world and remains a major public health problem in Sub-Saharan Africa. First-line treatment of uncomplicated malaria includes the use of artesunate and amodiaquine. However, the existence of counterfeit and substandard artesunate and amodiaquine in the market may lead to therapeutic failures or development of resistance when consumed. The aim of the study was to examine the pharmaceutical equivalence of different brands of artesunate and amodiaquine tablets and, their bioavailability and tolerability when given as monotherapy and combination therapy. Fifteen brands of artesunate and five brands of amodiaquine tablets selected randomly were obtained from retail drug outlets in Ogun, Oyo and Lagos states in South western Nigeria and were subjected to various physicochemical tests including drug content, disintegration and dissolution times. The bioavailability after oral administration of single doses of artesunate (200mg), amodiaquine (600mg), their fixed combination (200mg/612.6mg), and non-fixed combination (200mg+600mg) as measured by high performance liquid chromatography of plasma samples and tolerability were compared. Sixteen healthy male volunteers aged between 18 and 45 years distributed into four groups received treatments at four different occasions in an open label, Latin square, 4-phase, cross-over study. Absorption was determined from area under the plasma drug concentration-time curves (AUC), peak plasma concentration (Cmax) reached and time taken to reach peak plasma concentration (Tmax). Impairment of absorption was indicated by at least one statistically significant parameter. Biochemical test was measured using serum albumin while body fat was derived from the body mass index. Data collected from physicochemical tests were evaluated using correlation and Chi square analyses while those of serum albumin and body fat, parent drugs and their main metabolites(dihydroartemisinnin and desethylamodiaquine) were assessed using logistic regression, Students’ t-test and ANOVA. Physicochemical tests revealed that 33.0% of the artesunate tablets and 80.0% of the amodiaquine tablets analyzed met compendial standards. Minimum absorption occurred when tablets were given as monotherapy and in combination. The bioavailability of artesunate when given in fixed combination with amodiaquine was lowered (Cmax ratio-76.4%, p<0.001) compared with monotherapy. Taking amodiaquine in fixed combination with artesunate markedly increased its bioavailability (AUC ratio-159.9%, p<0.001) when compared with monotherapy. However, concurrent administration of artesunate in non-fixed combination with amodiaquine reduced its bioavailability (Tmax ratio-209.7%, p<0.001) when compared with monotherapy. The bioavailability of amodiaquine was about twice as high when given in non-fixed combination (AUC ratio-195.4%, p<0.05) compared with monotherapy. Adverse events of concern were anaemia (81.25%), asthenia (62.5%) and neutropenia (25%). Asthenia was largely correlated with serum albumin in volunteers that took fixed dose combination (OR=9.3, p<0.05). Adverse effects were increased in volunteers that had higher body fat percentage (OR= 0.571, p>0.05). Pharmaceutically inequivalent and subpotent artesunate and amodiaquine tablets are in circulation in Southwestern Nigeria and this suggests the need for regulatory authorities to rigorously monitor their quality. There was severe impairment of rate and extent of absorption as a result of co-administration of the drugs. It is therefore recommended that artesunate should not be coadministered with amodiaquine in clinical setting.